(untitled) (KULT_online, 2014)
The present volume tackles complex issues of contemporary genre theory. It provides overviews of such important topics as the evolution of genres, metaization, hybridization, cognitive approaches, and medialization as well as Bakhtin’s genre theory. Apart from summing up the most important points of a variety of theoretical approaches to genre, it opens up perspectives for further research. In addition, a wide range of case studies provides insights into how theoretical frameworks can be applied to the analysis of specific texts.